Efektivitas Penegakan Hukum bagi Pelaku pelecehan Seksual pada Anak Ditinjau dari Hukum Pidana - Duwini Irawati; Grahadi Purna Putra (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
Law enforcement against perpetrators of child sexual abuse is a crucial issue in the criminal justice system. In the context of criminal law, child sexual abuse is categorized as a serious crime that harms victims physically, psychologically, and socially. The effectiveness of law enforcement can be seen from several aspects, including the existence of strict regulations, implementation of the law by law enforcement officers, and restoration of victims' rights. Criminal law in Indonesia has provided protection through statutory regulations such as Law Number 35 of 2014 concerning child protection, Law Number 12 of 2022 concerning criminal acts of sexual violence and the Criminal Code (KUHP). Criminal law in Indonesia has provided protection through regulations that regulate severe sanctions against perpetrators of sexual abuse, including imprisonment and fines. However, challenges in its implementation often arise, such as weak supervision, lack of evidence, or cultural barriers that prevent victims from reporting. The often protracted judicial process is also an obstacle to providing fast and effective justice. The effectiveness of law enforcement also depends on the synergy between law enforcement officers, the community, and the government. Preventive efforts through education and public awareness campaigns can reduce crime rates, while strict punishments for perpetrators are expected to provide a deterrent effect.